Prevalence, Risk Factors, and Outcomes of Delirium in Mechanically Ventilated Adults*. Issue 3 (March 2015) - Mehta, Sangeeta; Cook, Deborah; Devlin, John W.; Skrobik, Yoanna; Meade, Maureen; Fergusson, Dean; Herridge, Margaret; Steinberg, Marilyn; Granton, John; Ferguson, Niall; Tanios, Maged; Dodek, Peter; et al.
Abstract : Objective: Delirium is common during critical illness and associated with adverse outcomes. We compared characteristics and outcomes of delirious and nondelirious patients enrolled in a multicenter trial comparing protocolized sedation with protocolized sedation plus daily sedation interruption. Design: Randomized trial. Setting: Sixteen North American medical and surgical ICUs. Patients: Four hundred thirty critically ill, mechanically ventilated adults. Interventions: All patients had hourly titration of opioid and benzodiazepine infusions using a validated sedation scale. For patients in the interruption group, infusions were resumed, if indicated, at half of previous doses. Delirium screening occurred daily; positive screening was defined as an Intensive Care Delirium Screening Checklist score of 4 or more at any time. Measurements and Main Results: Delirium was diagnosed in 226 of 420 assessed patients (53.8%). Coma was identified in 32.7% of delirious compared with 22.7% of nondelirious patients ( p = 0.03). The median time to onset of delirium was 3.5 days (interquartile range, 2–7), and the median duration of delirium was 2 days (interquartile range, 1–4). Delirious patients were more likely to be male (61.1% vs 46.6%; p = 0.005), have a surgical/trauma diagnosis (21.2% vs 11.0%; p = 0.030), and history of tobacco (31.5% vs 16.2%; p = 0.002) or alcohol use (34.6% vs 20.9%; p = 0.009). Patients with positive delirium screening had longer duration of ventilation (13 vs 7 d; p < 0.001), ICU stay (12 vs 8 d; p < 0.0001), and hospital stay (24 vs 15 d; p < 0.0001). Delirious patients were more likely to be physically restrained (86.3% vs 76.7%; p = 0.014) and undergo tracheostomy (34.6% vs 15.5%; p < 0.0001). Antecedent factors independently associated with delirium onset were restraint use (hazard ratio, 1.87; 95% CI, 1.33–2.63; p = 0.0003), antipsychotic administration (hazard ratio, 1.67; 95% CI, 1.005–2.767; p = 0.047), and midazolam dose (hazard ratio, 0.998; 95% CI, 0.997–1.0; p = 0.049). There was no difference in delirium prevalence or duration between the interruption and control groups. Conclusion: In mechanically ventilated adults, delirium was common and associated with longer duration of ventilation and hospitalization. Physical restraint was most strongly associated with delirium. Abstract : Supplemental Digital Content is available in the text.